2020
DOI: 10.48550/arxiv.2001.01148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rigorous results for the electrical conductivity due to electron-phonon scattering

J. Amarel,
D. Belitz,
T. R. Kirkpatrick

Abstract: We present a rigorous solution of the Boltzmann equation for the electron-phonon scattering problem in three spatial dimensions in the limit of low temperatures. The different temperature scaling of the various scattering rates turns the temperature into a control parameter that is not available in classical kinetic theory and allows for a rigorous proof of Bloch's T 5 law. The relation between the Boltzmann equation and the Kubo formula is also discussed, as well as implications for the scattering of electron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Our technique for doing so is modeled after the analysis of the electron-phonon scattering problem in Paper I, which in turn is based on a mathematically rigorous treatment that was given in Ref. 9. What makes the exact solution possible is the zero eigenvalue of the collision operator Λ 0 , see Eq.…”
Section: Solutions Of the Kinetic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our technique for doing so is modeled after the analysis of the electron-phonon scattering problem in Paper I, which in turn is based on a mathematically rigorous treatment that was given in Ref. 9. What makes the exact solution possible is the zero eigenvalue of the collision operator Λ 0 , see Eq.…”
Section: Solutions Of the Kinetic Equationsmentioning
confidence: 99%
“…Only very recently has it been shown that a mathematically rigorous solution of the integral equation does indeed yield the Bloch T 5 law for the case of electron-phonon scattering. 9 In a previous paper 10 (to be referred to as Paper I) we have simplified and extended the method of Ref. 9.…”
Section: Introductionmentioning
confidence: 99%
“…The assumptions implicit in this exact solution can be eliminated, and the procedure made rigorous, if at the expense of substantially increased mathematical complexity, see Ref. 8. In Sec.…”
Section: Solutions Of the Integral Equationsmentioning
confidence: 99%
“…Only very recently has it been shown that a mathematically rigorous solution of the integral equation does indeed yield the Bloch T 5 law for the phonon contribution to the electrical resistivity ρ ∝ T 5 . 8 The purpose of the present paper is four-fold: First, we show that the method of Ref. 8 can be simplified substantially by making some assumptions about the collision operator that are common in theoretical physics, chiefly, the existence of a spectral representation.…”
Section: Introductionmentioning
confidence: 98%